Effectiveness of Waqf Asset Management by the Ministry of Religious Affairs Office in Efforts to Improve the Economic Welfare of the Community in Langkat Regency - Geri Cahya Wardana Butar-Butar; Abi Waqqosh (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
This study aims to determine the effectiveness of waqf asset management by the Langkat Regency Ministry of Religious Affairs Office in improving the economic welfare of the community. This study uses a qualitative approach with field research. Data collection techniques were carried out through observation, interviews, and documentation with informants consisting of the Langkat Regency Ministry of Religious Affairs Office, waqf administrators, and community members related to waqf asset management. The results show that waqf asset management by the Langkat Regency Ministry of Religious Affairs Office has been carried out through data collection activities, nazir guidance, supervision, and assistance with waqf land certification. However, the effectiveness of waqf asset management is still not optimal due to various obstacles such as the low quality of human resources managing waqf, lack of order in waqf administration, and minimal development of productive waqf. Most waqf assets are still used for traditional religious and social purposes so that their contribution to improving the economic welfare of the community is still relatively limited. In addition, the low public understanding of the importance of productive waqf management is also an obstacle to the development of waqf assets in Langkat Regency. To address these issues, the Langkat Regency Ministry of Religious Affairs Office has undertaken various efforts, including providing guidance to the nazir (Islamic trustee), promoting productive waqf, improving waqf administration, and collaborating with various relevant parties to optimize waqf asset management. Therefore, synergy between the government, the nazir (Islamic trustee), and the community is necessary to ensure that waqf asset management is more professional, productive, and oriented toward sustainably improving the economic well-being of the community.